School Leaders, Teachers, and Counselors’ Role in College and Career Readiness for First-Generation Students and Underserved Students by Promoting the Academy Modeling Concept - Hilliard, Ann Toler; Wharton-Beck, Aura (Advances in Social Sciences Research Journal, 2023)
Based on a grounded body of research, too many first-year freshmen students demonstrate not being ready to assume the responsibility of being academically ready for college and careers after leaving high school. Some of the readiness descriptions for college for first-year students are attitudinal and essential skills needed to participate proficiently in basic coursework in English composition and mathematics during the first year in college. A number of first-generation students do not demonstrate having the best skills needed to succeed in college and how to navigate ways in securing resources such as financial aid and other needed resources to be successful in college their first year especially. Too many students drop out of college during their first year (Choy, Horn, Nunez and Chen, 2000; Jackson, 2009). Research continues to show that there are some common indicators to observe by identifying students being at risk of dropping out of college during their first year. Is it important for all students and first-generation students to be prepared for college starting at an early age? Leaders, teachers, counselors and parents must ensure that all students are taking rigorous coursework and provide career awareness knowledge and opportunities to set the stage for college readiness and success. Leaders working collaboratively, especially with counselors for career information and teachers of mathematics and English composition are providing students with real-world skills and knowledge that will be needed in college are among the best practices to support student success as they leave high school and enter college. Students’ attitudinal behaviors, peers, and their families must be encouraged and given support in helping students to get to and succeed in college. At the secondary and post-secondary sites, it is essential for students to have a mentor, advisor, responsive curriculum, and appropriate resources to gain a greater chance for college success. This study looks at a variety of data to help communicate the meaning of college readiness based on four schools in two different states, first-generation students’ academic ability, social life, socioeconomic status, appropriate resources, and curriculum. Second, this study captures the role of school leaders, teachers, counselors, and parents who can all promote college readiness for students. This study is significant because it adds to the body of literature best practices on how to promote strategies that will effectively support college readiness for first-generation students using the academy modeling concept.